Determining treatment intensity in elderly patients with multiple myeloma. Issue 9 (2nd September 2018) - Salvini, Marco; D'Agostino, Mattia; Bonello, Francesca; Boccadoro, Mario; Bringhen, Sara
ABSTRACT: Introduction : In the majority of cases, multiple myeloma is a disease occurring in elderly patients. In the last decades, a major improvement in myeloma patients' outcome has been achieved with the introduction of several new drugs. However, this positive outcome was less likely to occur in elderly patients. Areas covered : An overall increase of myeloma cases in elderly patients is expected in the next years. This patient population is highly heterogeneous in terms of physiological functions and ability to resist stressing conditions such as myeloma and its treatment. While physicians cannot prevent the stress arising from the disease itself, the intensity of therapeutic approaches can be tuned according to patients' predicted tolerance. In this review, we focus on the assessment of patients' fitness and on available significant data on treatment efficacy and tolerability in elderly patients. Expert commentary : Fit, elderly patients should undergo full-dose therapy to maximize the depth of response, while intermediate and frail patients benefit from reduced-dose regimens in order to avoid toxicity and preserve quality of life. Ongoing trials will provide further evidence to individualize treatment on the basis of geriatric assessment and disease characteristics.